PERSEPSI MAHASISWA TERHADAP PENGAJAR PENUTUR JATI DALAM PEMBELAJARAN KETERAMPILAN BERBICARA BAHASA MANDARIN - Trihardini Ayu; Risky Wardhani; Magry Novdelia (Universitas Negeri Surabaya, 2022)
Recently in the era of globalization, mastery of foreign languages is immensely needed. In addition to English, a foreign language that has been recognized as an international language is Chinese. Since 2014 Universitas Negeri Jakarta (UNJ) has the Chinese Language Education Study Program (PSPBM UNJ) and in 2015 PSPBM UNJ began to involve native Chinese speaker teachers to teach Chinese speaking skills. Native speaker teachers are one of the influential factors in foreign language teaching and to determine the student's perception of them, especially in teaching Chinese speaking skills was the purpose of this study. This research was descriptive research with a survey method. The results showed that the perception of PSPBM UNJ students towards native Chinese-speaking teachers was generally positive. Students generally assumed that the teachers met the indicators contained in the pedagogical aspects, linguistic aspects, and socio-cultural aspects. Positive perceptions of native Chinese teachers had a good influence on the Mandarin language learning process at PSPBM UNJ. Keywords: perception, native Chinese speaker, Chinese speaking skills, language learning